Wandering spleen combined with pedicle torsion and splenic infarction: a rare case report and literature review - Cui, Qian; Xu, Xiaoyan; Li, Chang; Tang, Lihao (Frontiers in Pediatrics, 2024)
Wandering spleen (WS) concurrent with splenic pedicle torsion and infarction has been described rarely. We reported our experience in the diagnosis and treatment of such a condition in a 16-year-old girl with an acute abdominal pain. Plain CT scan showed the wandering of spleen from the left upper quadrant. Contrast enhanced CT indicated dilatation and distortion in the splenic vein, a counter-clockwise ‘whirl sign’ in the splenic pedicle, torsion of pancreatic tail and splenic infarction. The patient was diagnosed with WS combined with splenic pedicle torsion and splenic infarction, and underwent splenectomy for the treatment. She showed satisfactory outcome in the follow-up. To enhance our understanding of it, a comprehensive literature research was performed to summarize the clinical manifestations, treatment options and outcome among the adolescent patients.